Clonidine and dexmedetomidine for controlled hypotension during functional endoscopic sinus surgery: a comparative study - Erick Namegabe Mugabo; Yvette Masime Kulimushi; Gregor Pollach; Rania Abdelazim Sabra; Ragab Saad Beltagy; Furaha Nzanzu Blaise Pascal (BMC Anesthesiology)
Abstract Background Functional endoscopic sinus surgery (FESS) is minimally invasive, ambulatory endoscopic surgical procedure usually performed in most paranasal sinus diseases. Controlled hypotension during anaesthesia (hypotensive anesthesia) improves surgical field visibility and reduces risk of injuring surrounding structures. Clonidine (C) and dexmedetomidine (D) are both used to reduce blood pressure and heart rate while maintaining tissue perfusion. This study was conducted to evaluate the efficacy of clonidine compared to dexmedetomidine for controlled hypotension during FESS. Methods After ethical approval, 80 patients undergoing elective FESS were included in the study and randomly allocated to Group C or Group D. In Group C, 40 patients received intravenous clonidine with a loading dose of 3µg/Kg for 10 min and titrated maintenance dose of 0.4–0.8 µg/Kg/hour. In Group D patients received intravenous dexmedetomidine with a loading dose of 1µg/Kg for 10 min and titrated maintenance dose of 0.4–0.8µg/Kg/hour. The target was mean arterial blood pressure (MAP) between 55 and 65 mmHg and heart rate (HR) above 50 beats per minute. The primary outcome was blood loss. The secondary outcomes were surgical field quality assessed by Fromme Bezooart score, variations in MAP and HR intraoperatively, duration of surgery and anesthesia, and post-operative sedation assessed by Ramsay Sedation Score (RSS). Results Demographic data of both groups were comparable. The difference between both groups in terms of blood loss and surgical field quality was not statistically significant (p = 0.579, 1.000). MAP and HR were statistically significantly reduced to targeted level in both groups compared to baseline (p<0.001). Dexmedetomidine led to severe hypotension compared to clonidine, and the difference was statistically significant. Duration of return to baseline MAP and HR, duration of anesthesia and postoperative sedation were prolonged in group D compared to Group C. Conclusion Clonidine and dexmedetomidine provided good to excellent quality of surgical field visibility to surgeons during FESS. Dexmedetomidine produce more hypotension and bradycardia compared to clonidine which may be preferable for controlled hypotension in the setting of ambulatory surgery. However, considering the small sample of this study which could not detect small but clinically differences between both drugs, there is a need for a much larger and multicenter study to confirm these findings. Trial registration This trial was retrospectively registered in the Pan African Clinical Registry (pactr.samrc, ac.za) on 15 August 2024 under trial number PACTR202408565688611.